Nonlinear relationship between serum uric acid and body mass index: a cross-sectional study of a general population in coastal China - Hui Zhou; Zhen Liu; Zhong Chao; Yeqing Chao; Lidan Ma; Xiaoyu Cheng; Yangang Wang; Changgui Li; Ying Chen (Journal of Translational Medicine, 2019)
Abstract Background Conflicting evidence exists on the relationship between body mass index (BMI) and serum uric acid (SUA). Therefore, we aimed to evaluate the SUA–BMI relationship in a large-scale epidemiological survey in coastal China. Methods This survey was conducted among the general population in the coastal region of China from September 2014 to January 2015. SUA Levels were measured by the automatic Sysmex Chemix-180 biochemical analyzer. Results A total of 6098 men (BMI: 24.58 ± 3.74 kg/m2) and 7941 women (24.56 ± 3.64 kg/m2) were included in this study. A stronger positive BMI-SUA association was found for men than women (all P-values < 0.05). The piecewise linear spline models indicated a U-shaped relationship of SUA-BMI association for both men and women; and the lowest turning points were at 19.12 kg/m2 for men and 21.3 kg/m2 for women. When BMIs were lower than the nadir point, each 1 kg/m2 increase in BMI related to a 7.74-fold (95% CI − 14.73, − 0.75) reduction for men and 2.70-fold reduction (− 4.47, − 0.94) for women in SUA levels. Once the BMI was higher than the nadir point, each 1 kg/m2 increase in BMI was related to a 5.10-fold (4.44, 5.77) increment for men and 3.93-fold increment (3.42, 4.43) for women in SUA levels. The regression coefficient differences between the two stages were 12.84 (5.66, 20.03) for men and 6.63 (4.65, 8.61) for women. Conclusions A U-shaped relationship between BMI and SUA was found for both men and women; the association was stronger for men than women.